Apoptotic genes as potential markers of metastatic phenotype in human osteosarcoma cell lines - Zucchini, Cinzia (2008)
Metastasis is the most frequent cause of death among patients with osteosarcoma. We have previously demonstrated in independent experiments that the forced expression of L/B/K ALP and CD99 in U-2 OS osteosarcoma cell lines markedly reduces the metastatic ability of these cancer cells. This behavior makes these cell lines a useful model to assess the intersection of multiple and independent gene expression signatures concerning the biological problem of dissemination. With the aim to characterize a common transcriptional profile reflecting the essential features of metastatic behavior, we employed cDNA microarrays to compare the gene expression profiles of L/B/K ALP- and CD99-transfected osteosarcoma clones showing low metastatic ability with those of osteosarcoma cell lines showing contrasting behavior. Changes in gene expression were validated by real-time PCR and immunohistochemistry in independent samples. In our study we identified several differentially expressed genes (GADD45á, VCP, DHX9, survivin, á-catulin, ARPC1B) related to growth arrest and apoptosis. Most of these genes are functionally related with the nuclear factor (NF)-êB cell survival pathway that appeared to be inhibited in the less malignant osteosarcoma cells. Hence, we propose the inhibition of the NF-êB pathway as a rational strategy for effective management of human osteosarcoma.